2018
DOI: 10.3389/fphys.2018.00251
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Endurance Training During Childhood on Total Hemoglobin Mass

Abstract: Elite endurance athletes are characterized by markedly increased hemoglobin mass (Hbmass). It has been hypothesized that this adaptation may occur as a response to training at a very young age. Therefore, the aim of this study was to monitor changes in Hbmass in children aged 8–14 years following systematic endurance training. In the first study, Hbmass, VO2max, and lean body mass (LBM) were measured in 17 endurance-trained children (13 boys and 4 girls; aged 9.7 ± 1.3 years; training history 1.5±1.8 years; tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 35 publications
4
50
0
6
Order By: Relevance
“…In contrast to the abovementioned investigations, Prommer et al (17) very recently showed an effect of the activity level in children on the development of Hb mass (7% increase after 2.5 yr with >4 h of training per week) independent of physical growth. However, these findings are, on the one hand, based on young (preadolescent) children and, on the other hand, are equivocal to the training effect, since a longitudinal control group was missing.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast to the abovementioned investigations, Prommer et al (17) very recently showed an effect of the activity level in children on the development of Hb mass (7% increase after 2.5 yr with >4 h of training per week) independent of physical growth. However, these findings are, on the one hand, based on young (preadolescent) children and, on the other hand, are equivocal to the training effect, since a longitudinal control group was missing.…”
mentioning
confidence: 85%
“…All cardiovascular variables were scaled to LBM to account for general anthropometric growth in the observed age range and to correct for different amounts of body fat (17,28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean values for the [Hb] of the athletes of the three sports groups showed an average yearly increase of 4.4% in the swimmers, and 6.5% in the racket sports players, which was similar to published data for Hbmass, showing a mean value of ~430 g in 11–13-yr-old boys and ~370 g in 12–13-yr-old girls and boys [ 12 ]. Despite the general increase in hemoglobin mass with age, Prommer et al [ 11 ] did not find an independent statistical effect of age on Hbmass because, in their study, the effects fully overlapped with those of lean body mass (LBM) in such way that a 1 kg increase in LBM was associated with a 14.7 g increase in Hbmass. As literature has stressed the close relationship between the circulating testosterone levels and [Hb] [ 55 ], this leads to the hypothesis, that also the increase of [Hb] in young athletes is primarily affected by androgens [ 56 58 ].…”
Section: Discussionmentioning
confidence: 83%
“…Elite endurance athletes as well as elite game sport participants are characterized by a markedly increased O 2 transport capacity, hemoglobin concentration [Hb] and hemoglobin mass (Hbmass) [10,11]. Hbmass and hemoglobin concentration [Hb] belong to the major limiting factors of maximum endurance performance.…”
Section: Introductionmentioning
confidence: 99%